Remembering green - Beake, Lesley (London : Frances Lincoln Children's Books, 2010)
In the twenty-third century, global warming has caused a massive drought so the Tekkies seize an African girl and her lion cub in a terrible plan to restore the balance of the world.
Young Adult.
Young Adult
Keywords: Climatic changes -- Juvenile fiction; Princesses -- Juvenile fiction; Climatic changes -- Fiction; Princesses -- Fiction; Climate -- Fiction; Princesses -- Fiction; Table Mountain (KwaZulu-Natal, South Africa) -- Juvenile fiction; Table Mountain (KwaZulu-Natal, South Africa) -- Fiction; Table Mountain (KwaZulu-Natal, South Africa) -- Fiction